Ultra-wide-band structural slow light - Lai, Yiming; Mohamed, Mohamed Sabry; Gao, Boshen; Minkov, Momchil; Boyd, Robert W.; Savona, Vincenzo; Houdré, Romuald; Badolato, Antonio (Université d'Ottawa | University of Ottawa, 2018)
The ability of using integrated photonics to scale multiple optical components on a single monolithic chip offers key advantages to create miniature light-controlling chips. Numerous scaled optical components have been already demonstrated. However, present integrated photonic circuits are still rudimentary compared to the complexity of today's electronic circuits. Slow light propagation in nanostructured materials is a key component for realizing chip-integrated photonic devices controlling the relative phase of light and enhancing optical nonlinearities. We present an experimental record high group-index-bandwidth product (GBP) of 0.47 over a 17.7 nm bandwidth in genetically optimized coupled-cavity-waveguides (CCWs) formed by L3 photonic crystal cavities. Our structures were realized in silicon-on-insulator slabs integrating up to 800 coupled cavities, and characterized by transmission, Fourier-space imaging of mode dispersion, and Mach-Zehnder interferometry.